Wells to wheels: Environmental implications of natural gas as a transportation fuel. (October 2017) - Cai, Hao; Burnham, Andrew; Chen, Rui; Wang, Michael
Abstract: We assessed freshwater consumption, greenhouse gas (GHG) emissions, and air emissions of using compressed and liquefied natural gas (NG) as transportation fuels by three heavy-duty NG vehicles (NGV) types from a wells-to-wheels (WTW) perspective. We analyzed freshwater consumption for NG production in major U.S. shale gas plays from recent reports and studies. We reviewed recent literature quantifying methane leakage from the NG supply chain and vehicle use to improve the estimates of NGV GHG emissions. Results show that NGVs could reduce freshwater consumption significantly and offer air emissions reduction benefits compared to their diesel counterparts. NGV WTW GHG emissions are largely driven by the vehicle fuel efficiency, as well as methane leakage rates of both the NG supply chain and vehicle end use: we estimate WTW GHG emissions of NGVs to be slightly higher than those of the diesel counterparts given the estimated WTW methane leakage. NGVs utilizing the newest aftertreatment systems have lower WTW and vehicle operation NOx emissions across different duty-cycles and slightly lower WTW PM emissions than their diesel counterparts. We found that the cost-effectiveness of NGVs is impacted by incremental cost of NG storage tanks and the price difference between NG and diesel fuels. These findings for NGVs shed light on their environmental and economic impacts from a WTW holistic point of view. Highlights: Natural gas vehicles (NGVs) consume less WTW water relative to diesel counterparts. NGVs offers tailpipe and WTW NOx emission benefits. NGVs offers WTW PM emission benefits. Cost-effectiveness of NGVs is impacted by cost of NG storage tanks and fuel prices.